The Socio-Economic Life of Farmers: A Study of Social Change in the Ulu Saddang Village Community: Kehidupan Sosial Ekonomi Petani: Studi Perubahan Sosial Masyarakat Desa Ulu Saddang - Abd Majid (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2024)
The socio-economic life of the community is an important aspect in the structure of society, influenced by many factors such as economic activity, education level, type of work, and income level. In Ulusaddang Village, economic conditions play a crucial role in directing socio-economic change in the community. The purpose of this study is to determine the causes of socio-economic change and the impact of social change on the socio-economic life of farmers. This study uses a qualitative descriptive research type, which aims to describe in more detail the socio-economic life of farmers and social change. The theories used in the study are Piotr Sztompka's theory of social change and social exchange. Data collection techniques were carried out by means of observation, interviews, and documentation with data analysis techniques using data reduction, data presentation, and drawing conclusions. The results of this study indicate that the causes of socio-economic change in farmers in Ulu Saddang Village involve changes in community planting patterns, communication networks, and farmer education. The social changes that occur have a significant impact on the socio-economic life of farmers, including increased economic income, rapid exchange of information, increased farmer solidarity, shifts in values ​​and culture.